The hidden side of trust: Supporting and sustaining leaps of faith among firefighters - Pratt, Michael G.; Lepisto, Douglas A.; Dane, Erik (Administrative Science Quarterly)
Some occupations and organizations rely heavily on trust, as their members$1 (Broles involve risk and are interdependent. Trust can emerge from two sources: knowledge or evidence that is meaningful in that context, which has been studied extensively in the literature on trust, and faith, which has not. Through a multi-phase, largely inductive study of firefighters in the United States, we explore processes that facilitate and maintain leaps of faith. These processes are critical to trust under high uncertainty, when direct experience in a task domain is chronically limited, as is the case in our context because very few calls coming into a fire station are fire related. We suggest that leaps of faith are initiated and perpetuated through two sets of dynamics: supporting and sustaining. Supporting dynamics, such as telling stories about fighting fires, evoke domain-relevant standards that are applied to weak, non-domain-specific evidence, such as how routine tasks are performed at the fire station, to help members feel a sense of certainty about whom to trust. Sustaining dynamics both limit the impact of new evidence about trustworthiness and bolster one$1 (Bs sense of certainty surrounding existing evidence. These two sets of dynamics, embedded in broader task and occupational conditions, act together as a largely closed system that allows trustors to be at peace with the uncertainty surrounding trust assessments$1 (Bthey make leaps of faith possible by increasing certainty and inhibiting doubt. Our study helps address key questions in both psychological and sociological treatments of trust, exploring an enigmatic phenomenon core to the concept of trust but rarely examined. - Reproduced.s
Keywords: Faith; Trust; Fire